Determinants of the Development of Social Enterprises in the Lagging Region of Warmia and Mazury - Marian Olinski; Jarosław Mioduszewski; Peter Krištofík (Amfiteatru Economic)
Social enterprises in Europe are increasingly evolving into hybrid entities, simultaneously striving to attain both social and economic objectives. This transformation aligns them uniquely with the EU's Cohesion Policy, which seeks to reduce disparities and promote harmonious development across its regions. These hybrid enterprises can play a central role in this policy framework, particularly in regions marked by economic and social challenges. The main objective of the paper is to explore potential strategies to improve the performance of social enterprises operating in economically disadvantaged regions. The Warmia and Mazury region in Poland serves as a pertinent example in this context, marked by the highest unemployment rate in the nation alongside other notably weak economic indicators. These factors contribute to its designation as a “lagging region” by the European Union, thus making it a focal point for intervention under the Cohesion Policy. A key strategy suggested for regions facing these challenges involves fostering the growth of social enterprises, which are dedicated to addressing social issues through market-driven approaches. This study presents findings derived from a survey-based methodology. A comprehensive analysis was conducted on data sourced from 104 social enterprises in the Warmia and Mazury region, employing univariate descriptive statistical techniques. These techniques included the evaluation of frequency distributions, the calculation of percentages, means, standard deviations, and the application of nonparametric tests. The analysis provided insights that indicated that social enterprises that engaged in diversified business practices exhibited superior effectiveness compared to those with a narrower scope of activities. Furthermore, the perspectives of managers of these social enterprises were scrutinised, revealing a significant trend. The managers of diversified companies possessed a markedly optimistic outlook for future financial performance. However, it is important to note a critical limitation observed in the study – even the enterprises that demonstrated success within their local region faced challenges in replicating this success in other areas, suggesting a potential constraint in the scalability of their business models.